2014
DOI: 10.1002/ajmg.b.32240
|View full text |Cite
|
Sign up to set email alerts
|

ADHD pharmacogenetics across the life cycle: New findings and perspectives

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a complex and heterogeneous disorder, affecting individuals across the life cycle. Although its etiology is not yet completely understood, genetics plays a substantial role. Pharmacological treatment is considered effective and safe for children and adults, but there is considerable inter-individual variability among patients regarding response to medication, required doses, and adverse events. We present here a systematic review of the literature on ADHD phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 155 publications
1
37
2
1
Order By: Relevance
“…Current pharmacotherapy is not reliably guided by any disease-specific biomarkers or diagnostic tests, though advances in pharmacognetics may prove useful with further study 85 . It is possible that neurophysiological abnormalities assessed by TMS could also be used for this purpose 86 .…”
Section: Noninvasive Brain Stimulation In Adhdmentioning
confidence: 99%
“…Current pharmacotherapy is not reliably guided by any disease-specific biomarkers or diagnostic tests, though advances in pharmacognetics may prove useful with further study 85 . It is possible that neurophysiological abnormalities assessed by TMS could also be used for this purpose 86 .…”
Section: Noninvasive Brain Stimulation In Adhdmentioning
confidence: 99%
“…The majority of PGx-based studies have focused on existing ADHD medications, primarily methylphenidate, with the goal of identifying specific biomarkers of drug response, which are reviewed briefly here (see also Bruxel et al , 2014 56 ). One exception to this approach is a study from our group, which has used results from genomics analyses to identify novel drug targets for a genome-stratified ADHD sub-cohort.…”
Section: Presentmentioning
confidence: 99%
“…This would seem substantiated by a meta-analysis by Kambeitz et al, 2014 (n=1572) 60 , which found no evidence of a genotype-specific response to methylphenidate treatment (P>0.5). Similarly, VNTRs in the dopamine receptor D4 (DRD4) have been studied, again with no strong evidence of a genotype-specific response to methylphenidate 56 .…”
Section: Presentmentioning
confidence: 99%
“…Candidate genes each with 'small effect' might be by interacting with each other imposing an additive effect on ADHD etiology. In the last five years (2010)(2011)(2012)(2013)(2014)) several pharmacogenetic studies have been published with regard to gene x gene and gene x environment interactions (Bruxel et al, 2014).…”
Section: Gene-gene Gene-environment Interaction and Serotonergic Genesmentioning
confidence: 99%